2023
DOI: 10.1177/0258042x231152321
|View full text |Cite
|
Sign up to set email alerts
|

Analysing Determinants of Employee Performance Based on Reverse Mentoring and Employer Branding Using Analytic Hierarchical Process

Alpana Agarwal,
Divina Raghav

Abstract: The COVID-19 pandemic has forced companies to change the way they operate. It has accelerated the shift from conventional to digital business processes. Human resource management is at the centre of such extraordinary changes, where digital solutions can help employees to effectively manage them. Two major aspects that have grabbed the researchers’ attention here are reverse mentoring and employer branding initiatives. This paper is an attempt to test whether the determinants of employer branding and reverse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…The findings in Table 6 show that university performance model as a function of employee coaching, yielded an R 2 value of 0.764. This is an indication that 76.4% of the variation in performance of universities in Tanzania can be explained by employee coaching, a position also maintained by the study conducted by Agarwal and Raghav (2023), who suggested that employee coaching was critical in ensuring organizations perform best.…”
Section: Regression Analysis 451 Model Summarymentioning
confidence: 74%
“…The findings in Table 6 show that university performance model as a function of employee coaching, yielded an R 2 value of 0.764. This is an indication that 76.4% of the variation in performance of universities in Tanzania can be explained by employee coaching, a position also maintained by the study conducted by Agarwal and Raghav (2023), who suggested that employee coaching was critical in ensuring organizations perform best.…”
Section: Regression Analysis 451 Model Summarymentioning
confidence: 74%
“…Licensed Under Creative Commons Attribution (CC BY-NC) The findings in Table 5 show that university performance model as a function of employee mentoring, yielded an R 2 value of 0.766. This is an indication that 76.6% of the variation in performance of universities in Tanzania can be explained by employee mentoring, a position also maintained by the study conducted by Agarwal & Raghav (2023), who suggested that employee mentoring was critical in ensuring organizations perform best.…”
Section: Regression Analysismentioning
confidence: 77%
“…In a finding from a paper by (Agarwal & Raghav, 2023) states four key variables that improve employee performance. They are employee engagement, employee empowerment, development value, and interest value.…”
Section: Resultsmentioning
confidence: 99%